Introduction to environmental engineering . (3rd ed.) - Davis, Mackenzie Leo, 1941- ; Cornwell, David A., 1948- (WCB McGraw-Hill, 2020)
Introduction -- Hydrology -- Water treatment -- Water quality management -- Wastewater treatment -- Air pollution -- Noise pollution -- Solid waste management -- Hazardous waste management -- Ionizing radiation.